An Optically Isotropic Antiferroelectric Liquid Crystal (OI‐AFLC) Display Mode Operating over a Wide Temperature Range using Ternary Bent‐Core Liquid Crystal Mixtures. Issue 2 (7th February 2017) - Bergquist, Leah; Zhang, Cuiyu; Ribeiro de Almeida, Roberta R.; Pellegrene, Brittany; Salamonczyk, Miroslaw; Kim, Matthew; Hwang, Jung‐Im; Kim, Kyeong‐Jin; Lee, Joun‐Ho; Jákli, Antal; Hegmann, Torsten
Abstract: We report on the synthesis and characterization of bent‐core liquid crystal (LC) compounds and the preparation of mixtures that provide an optically isotropic antiferroelectric (OI‐AFLC) liquid crystal display mode over a very wide temperature interval and well below room temperature. From the collection of compounds synthesized during this study, we recognized that several ternary mixtures displayed a modulated SmCa PA phase down to below −40 °C and up to about 100 °C on both heating and cooling, as well as optical tilt angles in the transformed state of approximately 45° (optically isotropic state). The materials were fully characterized and their liquid crystal as well as electro‐optical properties analyzed by polarized optical microscopy, differential scanning calorimetry, synchrotron X‐ray diffraction, dielectric spectroscopy, and electro‐optical tests. Abstract : Perfectly black in any viewing angle : An optically isotropic antiferroelectric liquid crystal display mode is realized by using ternary bent‐core liquid crystal mixtures, forming a polar antiferroelectric tilted smectic phase. The newly developed mixtures show an ideal tilt of 45°, permitting perfect black in the transformed, electric‐field OFF state, and switch under an applied electric field from below room temperature to 100 °C.